Permainan Sebagai Metode Pendekatan Edukasi Kesehatan Jantung Lansia - Widayani Yuliana; Sisilia Indriasari (Universitas Baiturrahim, 2026)
The elderly population has shown an increase compared to the previous year. Along with this increase in the number of elderly, non-communicable diseases (NCDs), especially heart disease, have become one of the largest contributors to the decline in elderly health. To anticipate delays in treatment, educational breakthroughs are needed to encourage the public to detect early and adopt anticipatory lifestyle habits to better control triggers of heart disease. The purpose of this education is to determine the level of elderly knowledge about heart disease using the game method. Games are one approach to stimulate the elderly's brain. Based on the results of the activity, the level of elderly knowledge before the education was obtained, 19 of 30 elderly (63%) had sufficient knowledge. After the education, 27 (90%) elderly had good knowledge. The methods used during the education were games, questions and answers, and competitions. Games are the method of choice in increasing elderly knowledge because the method is presented in an interesting and easily accepted manner. This method can be an option for local community leaders in developing activity programs when providing education to the elderly.